Exploring the regenerative capacity of the spleen following irradiation - Short, Christie T. M.; O’Neill, Helen C.; Tan, Jonathan K. H. (Frontiers in Hematology, 2024)
IntroductionHaematopoietic stem cell transplantation (HSCT) is commonly used to treat patients with haematological disorders. Myeloablative conditioning is an important preparation for patients receiving haematopoietic stem cells (HSC) or haematopoietic stem and progenitor cells (HSPC). While widely successful, HSCT is still associated with high rates of mortality. The recovery time between complete myeloablation and haematopoietic recovery is a large factor in the recovery rate. Successful engraftment of HSC is also directly correlated with the number of HSC niches available. This highlights the importance of the haematopoietic niche and its recovery from myeloablation as an important therapeutic target.MethodsThis murine model study specifically considers changes in spleen tissue architecture and cellular composition involving stromal and vascular cells that occur following lethal irradiation.ResultsSpleen recovered fully between 4- and 8-weeks after irradiation due to reconstitution by HSPC from bone marrow. Specific temporal changes in spleen architecture were identified, and these were linked to the cell types that constitute the white pulp, red pulp and marginal zones. Mesenchymal stromal cells returned before endothelial cells, and reticular cell types recovered more quickly in spleen following irradiation. Losses in gp38+ fibroblastic reticular cells and MAdCAM-1+ marginal reticular cells were associated with loss of the white pulp in the first 4 weeks following irradiation. White pulp was restored following recovery of supporting reticular cells.DiscussionThis study tests how spleen regeneration following a lethal dose of irradiation can be influenced by co-infusion of bone marrow HSPC together with either neonatal spleen stromal cells, or cells of the stromal STX3 line. Both the infusion of neonatal spleen stromal cells and STX3 stromal cells hastened recovery of both mesenchymal and vascular compartments. Following neonatal spleen stromal cell infusion, endothelial cells increased early, but a delay in structural reformation of distinct red and white pulp areas was found. Results from this study show that spleen regeneration can be influenced and even hastened through cellular therapy. Neonatal spleen stromal cells, co-infused together with HSPC following irradiation conditioning, represent a potential therapeutic opportunity for hastening spleen regeneration.